Physical activity, sedentary time, and risk of colorectal cancer: the Singapore Chinese Health Study. Issue 6 (November 2017) - Eaglehouse, Yvonne L.; Koh, Woon-Puay; Wang, Renwei; Aizhen, Jin; Yuan, Jian-Min; Butler, Lesley M.
Abstract : Singapore has experienced a marked increase in colorectal cancer incidence over the past 40 years. Evidence from prospective studies in Western Europe and the USA suggests that low physical activity and high amounts of sedentary time are associated with increased colorectal cancer risk. The aim of this study is to evaluate these relationships in an Asian population. The Singapore Chinese Health Study enrolled 63 257 adults between 1993 and 1998. At enrollment, participants reported past year physical activity and time spent sitting. Incident colorectal cancers ( n =1994) were identified through 31 December 2014. Cox proportional hazards models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) adjusted for potential confounders. Any strenuous–vigorous or moderate physical activity was reported by 13.7 and 22.1% of the cohort, respectively. Strenuous–vigorous physical activity was associated with statistically significant reduced colorectal cancer risk (HR=0.85; 95% CI: 0.74–0.99 for ≥0.5 h/week vs. none), but moderate was not. In analysis stratified by time spent watching television, an inverse relationship between moderate physical activity and colorectal cancer risk (HR=0.86; 95% CI: 0.72–1.01 for ≥0.5 h/week vs. none) was observed for those who reported at least 3 h/day sitting watching television ( P interaction =0.042). Participation in strenuous–vigorous physical activity, such as jogging, swimming, or heavy manual labor, was associated with reduced colorectal cancer risk among Singapore Chinese. Further research on physical activity and sedentary behaviors, independently and in combination, and colorectal cancer risk in Asian populations is needed. Abstract : Supplemental Digital Content is available in the text.